TAX REFORM PAJAK PENGHASILAN - Fadjar - Harimurti (Universitas Slamet Riyadi, 2010)
ABSTRACT Tax for Indonesia state function as budgeter and regulatory. The first tax function finally place tax as governmental pledge to yield acceptance which at the farthest from tax sector. To realize this matter government make a policy in the form of tax reform. Tax reform for the income tax for example change of tax rate, extention of tax subject and object, gift of taxation facility and priority for the case of is certain. From here can be seen that target of tax reform is to realize goals acceptance of state. Keywords: Tax reform, budgeter function, regulatory function.